1994
DOI: 10.1055/s-2007-1023569
|View full text |Cite
|
Sign up to set email alerts
|

Oligohydramnion - Perinatale Komplikationen und Erkrankungen bei Mutter und Kind*

Abstract: In our study, complications of oligohydramnios were examined. In medical records of all 5,210 deliveries of our department between 1987 and 1990 181 cases of oligohydramnios were identified. The diagnosis was confirmed by ultrasound and based on the method described by Mannings and Platt: amniotic fluid depots of less than 1 cm were defined as oligohydramnios. All 181 cases met the above definition, which results in an incidence of 3.5% pregnancies with reduced amniotic fluid. We examined the records of mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…12 reported very high (87.7%) perinatal mortality in their study. Wolff F et al 13 found that the perinatal mortality in their study was 7.2%. Apel-Sarid L et al 14 found that the perinatal mortality was 9.9%.…”
Section: Discussionmentioning
confidence: 77%
“…12 reported very high (87.7%) perinatal mortality in their study. Wolff F et al 13 found that the perinatal mortality in their study was 7.2%. Apel-Sarid L et al 14 found that the perinatal mortality was 9.9%.…”
Section: Discussionmentioning
confidence: 77%
“…24 Perinatal mortality in our study was 7.7% this was similar to study done by Wolff F et al in which perinatal mortality was 7.2%. 25 …”
Section: Discussionmentioning
confidence: 99%
“…14 Wolff F et al found that the perinatal mortality in their study was 7.2%. 15 Apel SL et al found that the perinatal mortality was 9.9%. 17 The lack of amniotic fluid allows compression of fetal abdomen, which limits the movement of the diaphragm.…”
Section: Perinatal Outcomementioning
confidence: 98%